PENGARUH PENERAPAN THERAPY ASERTIF TERHADAP PERUBAHAN PIKIRAN DAN PERILAKU ANAK USIA REMAJA - Anisah, Nur ANISAH (POLITEKNIK KESEHATAN KARYA HUSDA YOGYAKARTA, 2025)
The emergence of the phenomenon of juvenile delinquency tendencies (who are still students) has recently become a worrying problem from both educational, psychological, social and cultural perspectives. Teenagers' lives are marked by various kinds of juvenile delinquency, which is evidence of weak morality and personality in adolescence. Assertiveness or assertive behavior is behavior that displays courage honestly and openly when expressing desires, feelings and all thoughts as they are, without offending other individuals and still paying attention to one's own rights. Objective: To determine the effectiveness of assertive training therapy in changing thoughts and behavior. Research Method: This research design is Quasi Experimental Pre-Post Test With Control Group. This research compares two groups of school-aged children who experience learning difficulties at MTS Asyifa Albarokah. Results: The results of the analysis showed assertive behavior before the assertive training therapy was carried out, whereas after the assertive training therapy the assertive behavior was carried out in the assertive category. Conclusion: The results show that the alpha value is <0.05, while the p value obtained is 0.012, which means that there is a change or increase in adolescents' assertive behavior after being given assertive training therapy because the αlpha value is <0.05